2020
DOI: 10.1002/asjc.2483
|View full text |Cite
|
Sign up to set email alerts
|

A decentralized Nesterov gradient method for stochastic optimization over unbalanced directed networks

Abstract: Decentralized stochastic gradient methods play significant roles in large‐scale optimization that finds many practical applications in machine learning and coordinated control. This paper studies optimization problems over unbalanced directed networks, where the mutual goal of agents in the network is to optimize a global objective function expressed as a sum of local objective functions. Each agent using only local computation and communication in the networks is assumed to get access to a stochastic first‐or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…There was research focusing on the application of decentralized controller into the large-scale web-winding system [10]. On the other hand, the decentralized controller is an effective tool in dealing with the system with random disturbances, such as in the network area [11,12]. In decentralized control, the mean field game (MFG) is an alternative route when encountering large-scale agents, which was introduced by Lasry and Lions and Huang et al in 2007 to manage a large number of agents in a non-cooperative game problem [20,21].…”
Section: Literature Reviewmentioning
confidence: 99%
“…There was research focusing on the application of decentralized controller into the large-scale web-winding system [10]. On the other hand, the decentralized controller is an effective tool in dealing with the system with random disturbances, such as in the network area [11,12]. In decentralized control, the mean field game (MFG) is an alternative route when encountering large-scale agents, which was introduced by Lasry and Lions and Huang et al in 2007 to manage a large number of agents in a non-cooperative game problem [20,21].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Common multi‐AGV control systems can be classified into centralized systems and distributed systems. We choose to use the decentralized architecture as described in earlier studies [30, 31], as shown in Figure 1. The upper layer consists of a database that stores the necessary information for the environment and scheduling, a scheduling module, route planning module, and a supervisory control module.…”
Section: Problem Descriptionmentioning
confidence: 99%
“…Nowadays, mean-field control and game problems have attracted and gained more and more researchers' attentions, because of the extensive applications and significant theoretical values in many fields, such as economics, information technology, engineering, and system control [1][2][3][4][5][6][7][8][9][10]. There are two typically used problem frames and models for the mean-field control.…”
Section: Introductionmentioning
confidence: 99%